SISTEMATIKA SIKLUS PENULISAN AL-QUR’AN - Muhda Hadi Saputra; Rahmad (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
The codification of the Qur'an at the time of Usman bin Affan gave birth to the Ottoman Mushaf as a result. After the codification period, there was a heated discussion about the arrangement or order of the verses and letters in the Qur'an because the manuscripts compiled by Usman and his team were found to be different from the compositions of the verses and letters found in the manuscripts of other companions. The scholars agree on the tauqifiy of the arrangement of the verses of the Qur'an (in accordance with what was determined by the Prophet). Likewise, the arrangement of the letters in the Qur'an is understood as something that is tauqifiy from the prophet, although there are differences of opinion among the scholars, the arguments or arguments for the tauqifiy of the arrangement of the letters are stronger than the other 2 arguments which argue that the arrangement of the letters is ijtihadiy in its entirety or an opinion that states partly ijtihadiy and partly tauqif. Another discussion that arose was about the official Qur'an in Usman's manuscripts. The arguments and arguments put forward show that rasm al-Qur'an is a term for the pattern of writing al-Qur'an agreed upon by Usman not tauqifiy from the Prophet, following it is not obligatory, however, rasm of Usman still has to be used as a standard for writing patterns of the Qur'an .